Essential Role of the Innate Immune Adaptor RIP2 in the Response to Otitis Media - Kurabi, Arwa; Lee, Jasmine; Pak, Kwang; Leichtle, Anke; Ryan, Allen F (Frontiers in Genetics, 2022)
Intracellular nucleotide binding and oligomerization domain (NOD) and Toll-like (TLR) receptors have emerged as pivotal sensors of infection. Both Nod1 and Nod2 contain a caspase activation and recruitment domain (CARD) that interacts with the adaptor protein RIP2 (receptor-interaction protein-2). This leads to ubiquitination of RIP2 and in turn to the activation of NFκB and MAPK transcription factors, to command the host defensive response against pathogenic infections. RIP2 is also activated by TLRs 2 and 4, although the mechanism of this activation is less. The role of RIP2 in otitis media (OM) pathogenesis has yet to be examined. Herein, we used in vivo animal models including C57BL/6 wild-type (WT) and RIP2-/- knockout mice inoculated in the middle ear (ME) with non-typeable Haemophilus influenza (NTHi), a common human OM pathogen, to evaluate the expression of RIP2 and its signaling genes at the cellular level to determine the role of RIP2 in OM pathogenesis and recovery. The Nod1, Nod2 and Ripk2 genes are minimally expressed in the normal ME. However, they are strongly upregulated during acute OM, as are many genes related to RIP2 signaling. However, while signaling genes were expressed by various ME cell types, only mucosal epithelial and stromal cells expressed the NODs, RIP2 and signaling genes required for the activation of the host defensive response. Whereas WT mice clear ME bacteria and recover from OM within five days after infection, RIP2-deficient mice show persistent ME bacterial carriage and inflammation to at least 15 days. This includes significantly prolonged mucosal hyperplasia and ME leukocytic infiltration. Recruitment of macrophages is also delayed in comparison to WT mice. Thus, RIP2 is required to elicit a robust innate immune response that promotes bacterial clearance and increases host innate resistance. The results also identify the structural cells of the ME mucosa, as opposed to leukocytes, as the primary sites of NOD/RIP2 activity in the infected ME.